Implementation of Clinical Practice Guidelines for Empirical Antibiotic Therapy of Bacteremia, Urinary Tract Infection, and Pneumonia: A Multi-Center Quasi-Experimental Study - Pornpan Koomanachai; Jintana Srisompong; Sunee Chayangsu; Darat Ruangkriengsin; Visanu Thamlikitkul; Walaiporn Wangchinda; Rujipas Sirijatuphat; Pinyo Rattanaumpawan (MDPI AG, 2022)
A quasi-experimental study was conducted on the implementation of locally developed clinical practice guidelines (CPGs) for empirical antibiotic (ATB) therapy of common infections (bacteremia, urinary tract infection (UTI), pneumonia) in the hospitals from January 2019 to December 2020. The CPGs were developed using data from patients with these infections at individual hospitals. Relevant CPG data pre- and post-implementation were collected and compared. Of the 1644 patients enrolled in the study, 808 and 836 were in the pre- and post-implementation periods, respectively, and patient outcomes were compared. Significant reductions in the mean durations of intensive care unit stay (3.44 ± 9.08 vs. 2.55 ± 7.89 days; p = 0.035), ventilator use (5.73 ± 12.14 vs. 4.22 ± 10.23 days; p = 0.007), piperacillin/tazobactam administration (0.954 ± 3.159 vs. 0.660 ± 2.217 days, p = 0.029), and cefoperazone/sulbactam administration (0.058 ± 0.737 vs. 0.331 ± 1.803 days, p = 0.0001) occurred. Multivariate analysis demonstrated that CPG-implementation was associated with favorable clinical outcomes (adjusted odds ratio 1.286, 95% confidence interval: 1.004-1.647, p = 0.046). Among patients who provided follow-up cultures (n = 284), favorable microbiological responses were significantly less frequent during the pre-implementation period than the post-implementation period (80.35% vs. 91.89%; p = 0.01). In conclusion, the locally developed CPG implementation is feasible and effective in improving patient outcomes and reducing ATB consumption. Hospital antimicrobial stewardship teams should be able to facilitate CPG development and implementation for antimicrobial therapy for common infections.